Michel de Certeau among the ancients. The harmony of everyday life - Paranhos de Araújo Ribeiro, Clarissa (2025)
This text revisits the essay “Story Time”, a chapter from The Practice of Everyday Life, investigating the relevance of the issue of mimesis in the work of Michel de Certeau. It proposes to consider the author’s search for a style of writing that corresponds to the logic of tactics as a reflection on mimesis, but intertwined with another ancient notion dear to the author: that of métis. After presenting the concept of mimesis as conceived by ancient Greece and its relationship with métis, the importance of this notion in Certeau’s thematization of oral narratives is demonstrated, concluding that, by revisiting —without declaring or knowing it—the ancient notion of mimesis, the author characterizes tactics in everyday life as tending toward a particular form of harmony.